The presumption of innocence: Interpretation and application in online journalism - Wahyudi, Dicky; Sujoko, Anang; Ayub, Zainal Amin (Universitas Negeri Yogyakarta, 2022)
Implementation of the Presumption of Innocence by journalists has implications for the occurrence of trial by the press and potentially impacts social disharmony. This study aims to explain the interpretation of the presumption of innocence in journalism, and the understanding and application of the presumption of innocence by online media journalists. This research uses qualitative methods by utilizing two data collection techniques. Firstly, documentation that collects some related research about the Journalistic Codes of Ethics of the Press Council, PWI and AJI. Secondly, in-depth interviews with four online media journalists. The result shows that the literal interpretation of the presumption of innocence is a principle not to judge someone even though it is side by side with the principle of objectivity, covering both sides, mention of identity, and legal grammar. Online media journalists have a collective understanding of the presumption of innocence. However, the journalists have an authentic understanding that causes the different implementation of the presumption of innocence. Moreover, demands for faster news production, media agency policies, and personal interest from journalists also impact partial implementation. This research contributes by forming a model for applying the presumption of innocence for online media journalists to avoid trial by the press.